2005
DOI: 10.1097/01.alc.0000153551.11000.f3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescence: Booze, Brains, and Behavior

Abstract: This article represents the proceedings of a symposium at the 2004 Research Society on Alcoholism meeting in Vancouver, British Columbia, Canada, organized and chaired by Peter M. Monti and Fulton T. Crews. The presentations and presenters were (1) Introduction, by Peter M. Monti; (2) Adolescent Binge Drinking Causes Life-Long Changes in Brain, by Fulton T. Crews and Kim Nixon; (3) Functional Neuroimaging Studies in Human Adolescent Drinkers, by Susan F. Tapert; (4) Abnormal Emotional Reactivity as a Risk Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(153 citation statements)
references
References 120 publications
5
145
0
3
Order By: Relevance
“…These brain regions are among those that undergo considerable remodeling during adolescence [1,15,16,18,35,37,48,49] and, hence are likely targets for contributing to the disruption in social preference following chronic adolescent exposure to ethanol. Indeed, there are a number of reports that ethanol-induced damage in these and other brain regions may be more pronounced during adolescence than in adulthood [5,22]. For instance, Crews et al [5] demonstrated that 4 days of "binge" exposure to high doses of ethanol (9-10 g/kg/day) produces cell death, which is more evident in adolescent than adult rats in a number of frontal-anterior brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…These brain regions are among those that undergo considerable remodeling during adolescence [1,15,16,18,35,37,48,49] and, hence are likely targets for contributing to the disruption in social preference following chronic adolescent exposure to ethanol. Indeed, there are a number of reports that ethanol-induced damage in these and other brain regions may be more pronounced during adolescence than in adulthood [5,22]. For instance, Crews et al [5] demonstrated that 4 days of "binge" exposure to high doses of ethanol (9-10 g/kg/day) produces cell death, which is more evident in adolescent than adult rats in a number of frontal-anterior brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of high-risk populations (e.g., a family history of alcoholism) suggest impairments in frontal functioning are apparent prior to drug use exposure (Monti et al 2005;Schweinsburg et al 2005) and can predict later substance use (Deckel and Hesselbrock 1996; see also Ivanov et al 2008 for a review). Schweinsburg et al (2005) demonstrated that on a Go/No-go fMRI paradigm, adolescents with a positive family history of alcoholism demonstrated less inhibitory frontal response than those with no family history, despite similar task performance between groups.…”
Section: Executive Control Dysfunction In "At-risk" Individualsmentioning
confidence: 99%
“…Alcohol is the most commonly used substance by adolescents and a high percentage of consumption during this period occurs in bingeing or uncontrolled use (Witt, 2010). Importantly, an increasing number of studies have revealed that the adolescent brain is particularly vulnerable to alcohol-induced functional changes (Crews et al, 2007;Guerri and Pascual 2010;Monti et al, 2005;Philpot et al, 2009;Schindler et al, 2014;Squeglia et al, 2012;Zeigler et al, 2005). Moreover, adolescent alcohol use increases the likelihood of developing an alcohol use disorder (AUD) in adulthood (Blomeyer et al, 2013;Dawson et al, 2008;Hingson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%